Defining the surgical margins of adenoid cystic carcinoma and their impact on outcome: An international collaborative study. Issue 5 (2nd March 2017) - Amit, Moran; Na'ara, Shorook; Trejo–Leider, Leonor; Ramer, Naomi; Burstein, David; Yue, Ma; Miles, Brett; Yang, Xinjie; Lei, Delin; Bjoerndal, Kristine; Godballe, Christian; Mücke, Thomas; et al.
ABSTRACT: Background: The mainstay of treatment in adenoid cystic carcinoma (ACC) of the head and neck is surgical resection with negative margins. The purpose of this study was to define the margin status that associates with survival outcomes of ACC of the head and neck. Methods: We conducted univariate and multivariate analyses of international data. Results: Data of 507 patients with ACC of the head and neck were analyzed; negative margins defined as ≥5 mm were detected in 253 patients (50%). On multivariate analysis, the hazard ratios (HRs) of positive margin status were 2.68 (95% confidence interval [CI], 1.2–6.2; p = .04) and 2.63 (95% CI, 1.1–6.3; p = .03) for overall survival (OS) and disease‐specific survival (DSS), respectively. Close margins had no significant impact on outcome, with HRs of 1.1 (95% CI, 0.4–3.0; p = .12) and 1.07 (95% CI, 0.3–3.4; p = .23) for OS and DSS, respectively, relative with negative margins. Conclusion: In head and neck ACC, positive margins are associated with the worst outcome. Negative or close margins are associated with improved outcome, regardless of the distance from the tumor. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1008–1014, 2017